An Empirical Study on Peer-to-Peer Sharing of Resources in Mobile Cloud Environment - R. K. Nadesh; M. Aramudhan (Institute of Advanced Engineering and Science, 2018)
The increase usage of mobile users with internet and interoperability among the cloud services intensifies the role of distributed environemtnt in today’s real world application. Modern technologies are important for building rich, scalable and interoperable applications. To meet the requirements of client,the cloud service provider should offer adequate infrastructure especially under heavy multi-client load.To provide solution for large scale requirements and to statisfy the mobile client from the critical situation like lacking with bandwidth,connectivity issues,service completion ratio, we present adhoc virtual cloud model for different scenarios that include single and multiple client configurations with various file sizes of various file formats for retrieving files in the mobile cloud environement.We evaluate the strategies with the socket and RMI implemented using java and identify the best model for real world applications. Performance evaluation is done with the results obtained and recommends that when sockets and RMI can be appropriately used in peer-to-peer environment when the mobile user cannot connect directly to the cloud services.